SOCIALIZATION OF MANAGEMENT AS THE FUNCTIONINGOF SCHOOL SOCIAL BODIES FROM THE PERSPECTIVEOF NON-PUBLIC AND PUBLIC-SCHOOL TEACHERS - Berkowicz, Aleksandra (Management and Administration Journal, 2024)
Socialization was an important change in education management introduced after 1989. It provided an opportunity for schools to be managed by citizens and for citizens. Socialization was implemented by changing and modifying the tasks of social bodies that are part of a school’s organizational structure. The main aim of the work is to explore the issue of the role of school social bodies in the management of modern schools as a manifestation of the socialization of management. Thearticle poses the following research question: what is the involvement of social bodies in school management? The research used a quantitative strategy. The tool used to collect research material was a survey. The subjects of the research were teachersof public and private schools. The article shows that social bodies, as elements of the organizational structure, depending on the type of institution: public or non-public, have a different impact on the functioning of the studied school organizations. Their activity covers various areas of the school’s activities. School is an ideal platform, a laboratory, and a preliminary introductionto the world of democracy and its practice. One of the possibilities and at the same time a way through which attitudes and actions based on democratic values can be taught are social bodies operating in schools.